William Shakespeare's Star Wars : verily, a new hope - Doescher, Ian (Quirk Books, 2013)
A retelling of Star wars in the style of Shakespeare, in which a wise Jedi knight, an evil Sith lord, a beautiful captive princess, and a young hero coming of age reflect the valor and villainy of the Bard's greatest plays.